2020
DOI: 10.3390/admsci10040076
|View full text |Cite
|
Sign up to set email alerts
|

Quality Management Systems and Working Capital SMEs in GPO—A Case of Poland

Abstract: Working capital is designed to provide enterprises with financial security. Its level depends on the strategy of managing individual elements of working capital. An appropriate management strategy allows companies to obtain added working capital. Working capital management is a difficult process as it concerns both current assets and current liabilities. Therefore, company managers are constantly looking for solutions, methods and tools that will help them to manage their working capital. A quality management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
0
10
0
1
Order By: Relevance
“…The quality of financial statements can not only be useful for the transfer of information among different groups in the market but also can be an effective tool for evaluating the financial performance of companies and analyzing management decisions (Jerry and Saidu 2018). Some studies show that quality not only affects financial results but that the financial security of enterprises also reduces the risk of bankruptcy (Zimon and Zimon 2020;Fonseca and Domingues 2018). In order to effectively make decisions that reduce the financial risk, financial statements must be of high quality.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of financial statements can not only be useful for the transfer of information among different groups in the market but also can be an effective tool for evaluating the financial performance of companies and analyzing management decisions (Jerry and Saidu 2018). Some studies show that quality not only affects financial results but that the financial security of enterprises also reduces the risk of bankruptcy (Zimon and Zimon 2020;Fonseca and Domingues 2018). In order to effectively make decisions that reduce the financial risk, financial statements must be of high quality.…”
Section: Introductionmentioning
confidence: 99%
“…Ciertamente, este enfoque dificulta la revisión del sistema de calidad. Un muy buen ejemplo de gestión eficaz es el índice de rotación de pasivos en días (Zimon & Zimon, 2020).…”
Section: Estrategias Autoresunclassified
“…Tahir and Anuar (2016) added control variables to the analysis of working capital components and found that the growth of sales and fi rm size had positive association with profi tability, while the fi nancial debt ratio, gross domestic product, infl ation and interest showed negative results. Talonpoika (2014) stressed the necessity of taking advance payments into account as part of working capital, Farshadfar and Monem (2019) examined the relative importance of working capital accruals and deferrals, Zimon (2020) or Yousaf et al (2021) identifi ed the specifi cs of working capital management for fi rms implementing quality management, Madhou et al (2015) examined the impact of whether a fi rm is profi table/loss-making in the long term on the amount of working capital, and Habib and Huang (2018) showed that exports are an important component aff ecting working capital. In the case of export fi rms, the authors identifi ed a curvilinear relation between profi tability and working capital.…”
Section: Theoretical Backgroundmentioning
confidence: 99%